Face recognition by random method - Myo Khine. (2008)
From the theoretical analysis, we present the Null Random Search Direction algorithm and the most suitable situation for Null Random Search Direction. Our method is simpler than all other Null space approaches. It save the computational cost and maintains the performance simultaneously. The novel approach eigenvalue analysis and is also applicable to the large sample size problem. Experiments are carried out on different face data sets to demonstrate the effectiveness of the proposed methods.